Complicated giant diaphragmatic hernia, a rare but serious entity with complex repair - Baeza Carrión, Ana; Saeta Campo, Rebeca; Cornejo López, María de los Ángeles; Soler Ferriz, Vicente; Velayos García, Paula (Cirugía del Uruguay, 2020)
A 68-year-old man with COPD and right lung adenocarcinoma treated with chemoradiotherapy. He came to the emergency room for intense epigastric pain of 12 hours of evolution, without previous trauma. An urgent CT scan revealed a left anterior diaphragmatic herniation with abundant intrathoracic jejunal loops next to the colonic splenic flexure (Fig. 1, 2 and 3). They present marked dilation, interase fluid and a change in caliber, compatible with torsion of the mesenteric pedicle, obstruction and intestinal distress. He was operated on urgently, showing a non-traumatic hernial ring (congenital, probably Bochdalek) that compresses and necrotic the jejunum and splenic flexure. Hernia repair was performed with intestinal and segmental colon resection. Diaphragmatic hernia repair included exposure of the defect and continuous suture with resorbable material, avoiding the placement of prosthetic mesh due to the high risk of intestinal anastomosis leakage and subsequent infection. Favorable postoperative evolution, currently being followed up in consultations.